Food sovereignty in local development - Vergara-Romero, Arnaldo; Sorhegui-Ortega, Rafael; Salvador-Guerra, César (Journal of the University of Zulia, 2021)
This article contains a perspective of Food Sovereignty from local development, where the first concept complements the indistinct territorial development at the scale that is managed. It is very imperative that to evaluate the potentialities of local development, the right to food must be used as a pillar, since this is a substantial and evident problem at the present time worldwide, this problem is nutritional deficiency. It is also analyzed that this social metabolism can help to find a solution from the local to the regional and even the global, complementing the two concepts for the benefit of society. The type of methodology that was used consisted of a systematic review of updated information in academic articles on Food Sovereignty and Local Development, which was consulted in specialized databases such as Scopus and Web of Science